Examining the Contribution of Protected Area-Based Tourism to Sustainable Development Goals - PHIRI, Mercy; BELLO, Felix G.; LAMBULIRA, Mathews; MANUEL, Isobel (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025, 2025)
This paper examines the contribution of protected area-based tourism to Sustainable Development Goals (SDGs) at Lake Malawi National Park in Malawi, focusing on environmental, economic, and social sustainability. Adopting a qualitative exploratory cross-sectional design within an interpretive paradigm, the research engaged diverse stakeholders to explore tourism’s contribution to SDGs 1 (No Poverty), 8 (Decent Work and Economic Growth), 14 (Life Below Water), and 15 (Life on Land). The findings reveal that protected area-based tourism enhances local livelihoods by creating employment and entrepreneurship opportunities, facilitates biodiversity conservation through tourism operators and community-led initiatives, and supports the ecological health of Lake Malawi through sustainable tourism practices. Moreover, the study underscores the critical role of local community participation in tourism development and conservation, reinforcing the interconnectedness of social, economic, and environmental sustainability. By integrating these dimensions, Lake Malawi National Park serves as a model for leveraging tourism as a tool for sustainable development. The study calls for sustained investment in protected area-based tourism to maximize its benefits and ensure equitable distribution of tourism-generated resources, ultimately driving progress towards the SDGs and fostering long-term conservation and community resilience.